Investigation of electrospun nanofibers with an electrified non-Newtonian jet using differential quadrature method. (5th April 2018) - Valipour, P.; Tahvili, A.; Mohsenian, S.; Atouei, S.A.; Khosravi, M.
Abstract: In this paper, the influence of non-Newtonian rheology of nanofibers on electrospinning process is analyzed numerically. A simple and highly accurate numerical method called the Differential Quadrature Method (DQM), is used for solving the governing equations of electrospinning systems. The validity of the results of DQM solution are verified via comparison with experimental data and a good agreement between the present method and the experimental data is observed. The behavior of the elongation, velocity, stress and total force profiles with variation of some physical parameters are discussed in details. The results show that by increasing the values of yield stress, the fluid elongation is reduced significantly. Furthermore, it is found that Differential Quadrature Method can be easily extended to other strongly nonlinear equations and can be found widely applicable in engineering and science. Highlights: Polymer nanofibers in electrospinning process is studied. DQM is used to solve the governing equations of electrospinning system. Results show a good agreement between experimental data and numerical method.